Still Standing Defiantly: Guidelines for Reducing Inequality of Human capital in the Northeast of Thailand during the Covid-19 pandemic - Chamaratana , Thanapauge; Phatchaney , Kritsada; Prabnok, Puttharak; Jearviriyaboonya , Jakkrich; Meekaew , Nattapon (Journal of Ecohumanism, 2024)
This study aimed to develop an approach to reduce human capital inequality of marginalized people in the northeastern of Thailand during the Covid – 19 pandemics. This study employed a qualitative research methodology to collect data through focus group discussions with the focus group discussion guideline from a group of key informants who were stakeholders in urban development and the quality-of-life development in Nakhon Ratchasima Municipality, Khon Kaen Municipality, and Udon Thani Municipality, totaling thirty-six persons. The study results indicate that there were three approaches to reducing human capital inequality of marginalized people in northeastern Thailand during the Covid – 19 pandemic as were follows: a) Promote the civil society networks, 2) Develop Human capital of marginal households, and3) Develop a tripartite inequality reduction mechanism between government agencies, the public sector, and civil society to coordinate cooperation between agencies to share information and problems for further resolutions.